Ε–NTU relationships in parallel–series arrangements: Application to plate and tubular heat exchangers. (25th April 2016) - Fernández-Torrijos, M.; Almendros-Ibáñez, J.A.; Sobrino, C.; Santana, D.
Highlights: ε –NTU expressions for series–parallel heat exchangers. Analytical expressions of the effectiveness of Npa -1 pass PHEs. Algebraic expressions for PHEs with a low number of plates obtained numerically. Analytical expressions of the effectiveness of series–parallel tubular heat exchangers. Graphical Abstract: Abstract: The ε – NTU method has advantages over other methods because it does not require assumption of an outlet temperature to determine the duty of a heat exchanger. In this work, the ε – NTU method was used to obtain a general algebraic expression of the effectiveness of PHEs in the N p a pass-1 pass configuration as a function of the heat capacity ratio ( C *) and the number of transfer units ( NTU ). This expression is valid for PHEs with a high number of plates ( Np > 40). In addition, 1 pass-1 pass and 2 pass-1 pass PHEs were numerically analyzed to obtain an algebraic expression of the effectiveness of PHEs with a low number of thermal plates ( Np < 40) as a function of C *, NTU and the number of plates. Finally, the expression obtained for N p a pass-1 pass PHEs with a high number of plates was generalized for use in any heat exchanger with series–parallel configurations, such as series–parallel arrangements of double-pipe or shell-and-tube heat exchangers.